2018
DOI: 10.1002/er.4009
|View full text |Cite
|
Sign up to set email alerts
|

Design and performance study of a low concentration photovoltaic-thermal module

Abstract: Summary Compared with traditional photovoltaic‐thermal system, low concentration photovoltaic‐thermal systems install the low‐power concentrator (compound parabolic concentrator, Fresnel concentrator, miniature trough concentrator, etc) to improve system performance. In this paper, a baffle heat exchange channel was designed, which can decrease the temperature gradient of low concentration photovoltaic‐thermal module in the flow direction, based on the traditional flat‐box photovoltaic‐thermal collector. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The unimproved total HTC for the coolant ()hitaliccf comes from the Dittus‐Boelter equation which is widely mentioned in most heat transfer book such as: hcf=KDh()0.023Re0.8Pr0.4 with italicPr=μCpK, italicRe=ρVwDhμ, and Dh=4italicwh2w+2h, where μ , ρ , C p , and K are the dynamic viscosity, density, specific isobar heat capacity, and thermal conductivity, respectively; V w is the water velocity; w duct width; and duct height h .…”
Section: Mathematical Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The unimproved total HTC for the coolant ()hitaliccf comes from the Dittus‐Boelter equation which is widely mentioned in most heat transfer book such as: hcf=KDh()0.023Re0.8Pr0.4 with italicPr=μCpK, italicRe=ρVwDhμ, and Dh=4italicwh2w+2h, where μ , ρ , C p , and K are the dynamic viscosity, density, specific isobar heat capacity, and thermal conductivity, respectively; V w is the water velocity; w duct width; and duct height h .…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…The unimproved total HTC for the coolant h ′ cf comes from the Dittus-Boelter equation which is widely mentioned in most heat transfer book such as 32 :…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…Zhai 17 for instance evaluated the performance of a concentrator of solar radiation that employed a linear Fresnel lens. Zhang et al 22 improved the performance of the PV/T system through using a baffle heat exchange channel. The percentages of various kinds of energy losses are estimated.…”
Section: Introductionmentioning
confidence: 99%
“…MPCS was used as the cooling fluid by Qiu et al in a PV/T system and an experiment was proposed to validate the theoretical investigation. Zhang et al conducted an investigation on a low concentration PV/T module. The results indicated that the maximum thermal and electrical efficiencies of the module were 55.11% and 12.50%.…”
Section: Introductionmentioning
confidence: 99%